(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
A survey was performed to measure the anthropometric dimensions of 201 young men, with ages ranging from 18-28 years, in Western China. A total of 25 anthropometric dimensions were measured for these young men. Mean values, standard deviations, 5th, 50th and 95th percentiles for these anthropometric dimensions and 7 body proportions were determined. Subsequently, the anthropometric dimensions of these young men were compared with those from central and eastern regions of China and also national standards. It was found that the body shapes of the young Western Chinese men were significantly different from those of other regions. In addition, the following five factors were identified, according to a factor analysis of the data obtained in the study: waist girth, abdominal girth and waist height, as being the most important anthropometric variables to be considered when designing trousers.